2018
DOI: 10.1002/adfm.201805372
|View full text |Cite
|
Sign up to set email alerts
|

CelloMOF: Nanocellulose Enabled 3D Printing of Metal–Organic Frameworks

Abstract: 3D printing is recognized as a powerful tool to develop complex geometries for a variety of materials including nanocellulose. Herein, a one-pot synthesis of 3D printable hydrogel ink containing zeolitic imidazolate frameworks (ZIF-8) anchored on anionic 2,2,6,6-tetramethylpiperidine-1-oxylradicalmediated oxidized cellulose nanofibers (TOCNF) is presented. The synthesis approach of ZIF-8@TOCNF (CelloZIF8) hybrid inks is simple, fast (≈30 min), environmentally friendly, takes place at room temperature, and allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 69 publications
1
126
0
Order By: Relevance
“…2a, b), with the amount of HKUST-1 loaded onto the template increasing with increased reaction time. The as-obtained composites were tested for electrochemical [149] sensing of glucose, showing very promising activity with a relatively wide linear range (15.84 µM-5.62 mM), low limit of detection (4.8 µM), and a high sensitivity (28.67 µA mM −1 cm −2 ). The excellent electrocatalytic activity was attributed to the presence of macropores in the hierarchical structure which was led to improved mass transfer of the glucose.…”
Section: Hard Structural Templatingmentioning
confidence: 99%
“…2a, b), with the amount of HKUST-1 loaded onto the template increasing with increased reaction time. The as-obtained composites were tested for electrochemical [149] sensing of glucose, showing very promising activity with a relatively wide linear range (15.84 µM-5.62 mM), low limit of detection (4.8 µM), and a high sensitivity (28.67 µA mM −1 cm −2 ). The excellent electrocatalytic activity was attributed to the presence of macropores in the hierarchical structure which was led to improved mass transfer of the glucose.…”
Section: Hard Structural Templatingmentioning
confidence: 99%
“…16 Our group reported the 3D-printing of Cu-BTC MOF for the adsorption of organic dyes from solutions, 17 and Lyu et al reported a 3D-printed cobalt-based MOF embedded within an organic binder for energy storage applications. 18 More examples on 3D-printed MOFs were explored by Lawson et al and Sultan et al 19,20 Recently, our group, in collaboration with Amo-Ochoa and Zamora, also published the 3D-printing of a Cu 2+ coordination polymer for the colorimetric sensing of humidity and water. 21 In these prior works, the coordination polymers were synthesized prior to the printing, mostly in the form of particles, which were later dispersed within matrix forming materials, since the CP particles could not form a stand-alone 3D object without binders.…”
Section: Introductionmentioning
confidence: 99%
“…A similar binder‐free approach was shown for the MOF HKUST‐1 that was printed as a gel, although, with low resolution only on the millimeter scale . A somewhat different approach is based on the printing of a paste that consists of cellulose pulp fibers with surface‐grown MOF particles . Recently, also a covalent organic framework (COF) was printed from a pre‐polymerized precursor gel with a subsequent posttreatment to achieve the full formation of the accessible framework material in a 3D monolithic structure .…”
Section: Introductionmentioning
confidence: 99%